School Mental Health in Charters: A Glimpse of Practitioners from a National Sample - Jandel Crutchfield; Kate L Phillippo; Annahita R Ball (International Journal of School Social Work, 2022)
Charter schools are part of a global push for alternative governance models in public education. Even though U.S. charter schools enroll nearly 3.2 million children, little is known about school mental health (SMH) practice in charter schools. The current study was the first step in a line of inquiry exploring SMH and school social work practice in charter schools. Using cross-sectional survey research methods, the authors conducted brief one-time phone surveys with charter school social workers and counselors identified using a stratified random sampling strategy with national charter school lists. The final sample for analysis was 473 schools. Of these, 44.4% (n = 210) had a school social worker or counselor present at least one day per week, of whom 67 (30.5%) were school social workers. The school social work sample reported a number of job titles, including “school social worker” (67%) and many (13.4%) that were a variation of counselor (e.g., “behavioral counselor,” “social emotional counselor”). Half were employed by their school, five were employed by an outside organization contracted with the school and eight were employed by the school’s chartering organization. More than three-quarters (83%) had a master's degree in social work as their highest degree. Our findings provide a snapshot of the SMH and school social work workforce within the emerging practice setting of charter schools. Findings suggest that the SMH workforce may be professionally similar to those in traditional public schools, but with more flexibility for interprofessional collaboration, professional advocacy, and role definition. Other implications for research are also discussed.
Keywords: school mental health; charters; school social work